50 years of rational‐emotive and cognitive‐behavioral therapy: A systematic review and meta‐analysis. Issue 3 (12th September 2017) - David, Daniel; Cotet, Carmen; Matu, Silviu; Mogoase, Cristina; Stefan, Simona
Abstract : Objective: Rational emotive behavior therapy (REBT), introduced by Albert Ellis in the late 1950s, is one of the main pillars of cognitive‐behavioral therapy. Existing reviews on REBT are overdue by 10 years or more. We aimed to summarize the effectiveness and efficacy of REBT since its beginnings and investigate the alleged mechanisms of change. Method: Systematic search identified 84 articles, out of which 68 provided data for between‐group analyses and 39 for within‐group analyses. Results: We found a medium effect size of REBT compared to other interventions on outcomes ( d = 0.58) and on irrational beliefs ( d = 0.70), at posttest. For the within‐group analyses, we obtained medium effects for both outcomes ( d = 0.56) and irrational beliefs ( d = 0.61). Several significant moderators emerged. Conclusion: REBT is a sound psychological intervention. Directions for future studies are outlined, stemming from the limitations of existing ones.